Pengaruh Parental Influence, Personalitas Dan Penghargaan Finansial Terhadap Minat Mahasiswa Akuntansi Dalam Pemilihan Karir Menjadi Akuntan Publik - Octaviani Ismail, Yollanda; Tobing, Vargo Christian L. (SCIENTIA JOURNAL, 2024)
Research on accounting students' interest in a career to become a public accountant is one of the main things to do so that public accountants are in great demand by accounting student graduates. This research uses a quantitative approach. The population is students majoring in accounting in Batam City who are registered on the DIKTI website, learning year 2023/2024 with a total of 1,234 students. The results of the study through the t test, parental influence and personality variables partially did not have a significant effect on the interest of accounting students in becoming public accountants. Financial reward variable partially has a significant effect on the interest of accounting students in becoming public accountants. The results of the study based on the calculated F value on the three independent variables, namely parental influence, personality and financial rewards, simultaneously have a significant effect on the interest of accounting students in becoming public accountants. The Adjusted R Square result is 0.417 or 41.7%, means that the influence of parental influence, personality and financial rewards on the interest of accounting students is at a percentage of 41.7% and the rest is influenced by other variables as 58.3%.